EFEKTIVITAS CITRA MEREK TERHADAP PEMBELIAN MINUMAN RINGAN - Johanes Kurniawan; Devi Ratnasari; R Didiet Rachmat Hidayat (Institut Transportasi dan Logistik Trisakti, 2017)
The objective of this research is to find out the influence of sales promotion and brand image towards the decision of purchasing soft drinks. In this research, the writers used 2 methods of data collection which are data collecting using questionnaire and library research, and data analyzing using regression analysis techniques, correlation, coefficient determinant, and hypothesis testing. The results of the analysis and discussion show that there is a positive influence between sales promotion and brand image towards the decision of purchasing. It is shown in multiple linear regression equation that Y = 0.581 + 0.406X1 + 0.568X2. It means, if there is a change in X1 by one unit, consequently, there will be an increase in Y at 0.406. Moreover, if the brand image is increased by one unit, there will be an increase of Y at 0.568. Based on the correlation analysis, the value of R is 0.782, meaning that there is strong correlation between X1 and X2 towards Y. Coefficient determinant equals 61.1%. This means that the contribution of sales promotion and brand image towards the decision of purchasing is at 61.1% while the other 38.9% is affected by other factors. The partial hypothesis testing reveals that the Tstat of X1 equals 2.859 and Tstat of X2 equals 3.395 with Ttable is 2.021 where Tstat > Ttable and the result of Fstat = 30.606 and Ftable = 3.238, then Ho is rejected and Ha is accepted. This means there is a significant influence between sales promotion and brand image towards the decision of purchasing soft drinks.